2021
DOI: 10.1787/7a6d6736-en
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ professional learning study

Abstract: An international study into teachers' professional learningEffective teaching is at the heart of a successful education system. There is growing recognition that supporting teachers' professional learning from the beginning to the end of their career is critical to fostering high-quality teaching. The OECD Teachers' Professional Learning (TPL) study examines the policy environments that support teachers' professional growth by exploring common strengths and challenges in participating jurisdictions. In doing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(74 reference statements)
1
0
0
Order By: Relevance
“…Corroborating findings from other studies in the field [7,40,78,86], this study found that bringing principals together on a regular basis in itself seems enough to allow for beneficial personal outcomes that can provide mental support and ease professional grievances. Principal PLCs-and peer counselling more in general-have the potential to add to one's professional well-being by reducing a feeling of professional isolation which school principals often report [8] and by giving opportunities to ventilate both frustrations and concerns about school challenges, even if interactions are not that much structured or focussed on a specific policy question [87].…”
Section: Plc Output and Outcomessupporting
confidence: 76%
“…Corroborating findings from other studies in the field [7,40,78,86], this study found that bringing principals together on a regular basis in itself seems enough to allow for beneficial personal outcomes that can provide mental support and ease professional grievances. Principal PLCs-and peer counselling more in general-have the potential to add to one's professional well-being by reducing a feeling of professional isolation which school principals often report [8] and by giving opportunities to ventilate both frustrations and concerns about school challenges, even if interactions are not that much structured or focussed on a specific policy question [87].…”
Section: Plc Output and Outcomessupporting
confidence: 76%